Change in left ventricular function and outcomes following high-risk percutaneous coronary intervention with Impella-guided hemodynamic support - Farhan, Serdar; Freilich, Michael; Giustino, Gennaro; Vogel, Birgit; Baber, Usman; Sartori, Samantha; Kamran, Haroon; Mehran, Roxana; Dangas, George; Krishnan, Prakash; Kini, Annapoorna; Sharma, Samin K. (Frontiers in Cardiovascular Medicine, 2024)
High-risk percutaneous coronary interventions (HRPCI) are a potential treatment option for patients with reduced left ventricular ejection fraction (LVEF) and coronary artery disease. The extent to which such intervention is coupled with improvement in LVEF and associated with favorable outcomes is unknown. We aimed to characterize the incidence and correlates of LVEF improvement after Impella-guided HRPCI, and compare clinical outcomes in patients with versus without LVEF improvement. Data on consecutive patients undergoing Impella-guided HRPCI from a single center registry were analyzed. LVEF-improvement was defined as an absolute increase of LVEF of ≥10% measured at ≥30-days after intervention. The primary outcome was a composite of all-cause death, myocardial infarction or target vessel revascularization within 1-year. Out of 161 consecutive patients undergoing Impella-guided HRPCI from June 2008 to December 2017, 43% (n=70) demonstrated LVEF-improvement (baseline LVEF of 25.09 ± 6.19 to 33.30 ± 11.98 post intervention). Patients without LVEF-improvement had higher frequency of previous MI (61.5% vs. 37.1%, p=0.0021), Q-waves on ECG (17.6% vs. 5.7%, p= 0.024) and higher SYNTAX scores (30.8±17.6 vs. 25.2 ± 12.2; p=0.043). After correction of these confounders by multivariable analysis, no significant differences were found regarding the composite endpoint in patients with versus without LVEF-improvement (34.9% vs. 38.3%; p =0.48). Prospective studies with longer follow-up are needed to elucidate the impact of LVEF improvement on clinical outcomes.